The Five Non-Negotiables of Command Decision-Making: Turning Large-Scale Behavioural Observation into Operational Practice - Lamb, Katherine; Greatbatch, Ian; Perlini, Arthur; Hammar Wijkmark, Cecilia (Proceedings of the International ISCRAM Conference, 2026)
Public inquiries consistently show that emergency response failures stem less from technical limitations than from breakdowns in command decision making under pressure. Although incident command systems provide structural clarity, the behavioural foundations of reliable command remain insufficiently defined.This paper proposes a theory informed behavioural framework—the Five Non-Negotiables of command decision making— which organises the core behaviours that underpin each stage of the command cycle. Drawing on 30,843 structured assessments conducted across 43 UK Fire and Rescue Services between 2017 and 2024, we examine five interdependent capabilities: anticipatory situational awareness, adaptive strategy selection, objective based planning, communicative coordination and control, and dynamic review of decisions.Descriptive cross level patterns reveal persistent vulnerabilities in anticipation, communication, and review across all command tiers. These findings indicate that command reliability depends not on experience alone, but on the consistent enactment of key behavioural capabilities under uncertainty.